An approximated multi-state model for reliability evaluation of renewable generation - Chaiamarit K. (2017)
© 2016 IEEE. Reliability evaluation of power generation system is complicated with the integration of renewable sources, especially wind turbine and photovoltaics, whose generation characteristics are intermittent and time-varying. The concept of equivalent forced outage rate is conventionally utilized to simplify the computation burden. It is proposed to apply a multi-state model to express the variable generation of renewable sources. Number of de-rated states and corresponding de-rated capacities can be simplified by considering the plant factor. It is claimed that a number of certain capacity states may be neglected. Generation system reliability may be evaluated using two classical indices: loss of load probability and expected energy not supplied.